DEVELOPMENT OF GREEN TOURISM IN BUKHARA REGION BASED ON FOREIGN EXPERIENCES (Marketing Journal, 2026)
This article substantiates that green tourism is a development model that combines economic, social, and cultural interests while maintaining ecological balance at the international level. As a general conclusion of foreign approaches, it is shown that the factor of success is not "copying a ready -made model," but adaptation to regional conditions. The study identifies such mechanisms as green certificates, environmental transport, community -based participation, digital management, and improving "tourist quality" as priority areas. At the end of the article, based on forecast indicators expected № 1 -SON YANVA R, 202 6-YIL 290 until 2030 (number of tourists, tourism income, share of green facilities, investments, employment and environmental load), the regional strategic importance of green tourism is scientifically highlighted.
Keywords: green tourism; sustainable tourism; community -based tourism; green certification; green mobility; smart tourism; tourist flow